Social Mapping untuk Mengantisipasi Potensi Konflik Di Pertambangan Batubara Kabupaten Kutai Barat, Kaltim - Margana Wiratma (Humaniora, 2010)
This article tries to map the social condition by classifying the CSR (corporate social responsibility) main theories. The purpose of this social mapping is to identify the predefined indicators related to socio-political and cultural conditions. This method concentrates on a relative ranking of people’s socio-political and cultural conditions, rather than making an absolute assessment. The object of social mapping survey is the stakeholers and people related to the business activities of the coal mining corporates in the regent of Kutai Barat, Kalimantan Timur. By identifying the socio-political and cultural aspects, the corporate can anticipate and avoid any social conflicts about their business. The social mapping on socio-political and cultural aspect is very important for any coal mining corporates before launching their business on exploring as well as on exploiting by the CSR program. The CSR field presents not only a landscape of theories, but also a proliferation of approaches, which are controversial, complex and unclear. The social mapping on socio-political and cultural aspects is usefull for any coal mining companies at Kutai Barat in implementing the CSR. The CSR theory, in practice, presents four dimensions related to profit, political performance, social demands, and ethical values.